Company Characteristics as a Determinant of Tax Aggressiveness in Real Estate and Property Companies in Indonesia - Kautsar Riza Salman (Trunojoyo University of Madura, 2022)
This study aims to obtain empirical evidence regarding the effect of company characteristics on the level of tax aggressiveness. The level of tax aggressiveness is measured by the effective tax rate (ETR). Company characteristics in this study are represented by leverage, capital intensity, inventory intensity, and liquidity. The population in this study are all companies engaged in real estate and property and listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. This study's empirical finding is that leverage positively affects the effective tax rate (ETR). High leverage results in a lower level of tax aggressiveness because it is proven that companies pay higher income taxes. This study did not find the effect of capital intensity, inventory intensity, and liquidity on the level of tax aggressiveness. The policy implication for tax institutions is that high leverage on real estate and property companies does not necessarily increase the tendency of corporate tax aggressiveness; even the research results show the opposite result.